The Role of Vascular Endothelial Growth Factorin Thrombocytosis in Colorectal Cancer Patients: The Role of VEGF in Thrombocytosis - Subandrate Subandrate; Dwi Indira Setyorini; Mediarty Mediarty; Irsan Saleh (HM Publisher, 2018)
Backgorund: Colorectal cancer was included in a group of cancer with various complications. One complication that was often a cause of morbidity and mortality was thrombocytosis. In colorectal cancer, the incidence of thrombocytosis associated with the formation of blood vessels around the tumor or angiogenesis. Factors that played an important role in angiogenesis was vascular endothelial growth factor (VEGF). Methods: This study was an observational analytic research in colorectal cancer patients to determine the correlation levels of platelets and serum VEGF levels. A total of 33 patients with colorectal cancer at the Palembang Mohammad Hoesin Hospital be research subjects to examine the levels of platelets and levels of VEGF. The level of serum VEGF was performed using ELISA technique from SIGMA®. Results: The average level of the patient's platelets was281,090.9±105,860.8/mm3. In this study, two patients (6.06%) have thrombocytosis.The average serum levels of VEGF research subjects were 221.2 ± 152.8 pg/mL.Correlation test of levels of serum VEGF and platelets levels showed the value of p=0.040 (p> 0.05) and r = 0468. Conclusions: Thus, it can be concluded that in this research serum VEGF levels are almost always causes an increase in platelet levels in patients with colorectal cancer.